Structural disconnectivity in schizophrenia: a diffusion tensor magnetic resonance imaging study - Burns, J.; Job, D.; Bastin, M. E.; Whalley, H.; Macgillivray, T.; Johnstone, E. C.; Lawrie, S M. (British journal of psychiatry, 2003)
There is growing evidence that schizophrenia is a disorder of cortical connectivity. Specifically, frontotemporal and frontoparietal connections are thought to be functionally impaired. Diffusion tensor magnetic resonance imaging (DT-MRI) is a technique that has the potential to demonstrate structural disconnectivity in schizophrenia. To investigate the structural integrity of frontotemporal and frontoparietal white matter tracts in schizophrenia. Thirty patients with DSM-IV schizophrenia and thirty matched control subjects underwent DT-MRI and structural MRI. Fractional anisotropy - an index of the integrity of white matter tracts - was determined in the uncinate fasciculus, the anterior cingulum and the arcuate fasciculus and analysed using voxel-based morphometry. There was reduced fractional anisotropy in the left uncinate fasciculus and left arcuate fasciculus in patients with schizophrenia compared with controls. The findings of reduced white matter tract integrity in the left uncinate fasciculus and left arcuate fasciculus suggest that there is frontotemporal and frontoparietal structural disconnectivity in schizophrenia.